EKOLOGI KEONG DARAT DI TAMAN NASIONAL GUNUNG CIREMAI - Heryanto, Heryanto (Perhimpunan Biologi Indonesia, 2008)
ABCTRACTThe Ecology of Landsnail in Ciremai National Park. Twice fieldworks in order tocollect landsnails of Ciremai National Park were conducted, approximately in ArgamuktiVillage of western part of the park and Linggajati Village of eastern part of the park.They resulted 48 species of landsnails of 15 families. Thirty two species were found inArgamukti whereas 28 species were found in Linggajati. However, biodiversity indexescomparison for both locations were unsignificant at 95% level of confidence. Bothlocations were also populated by specific landsnails, only 40% of the whole landsnailswere live in Argamukti and Linggajati. The highest densities in entire locations weredominated by microsnails and mostly were live in lower latitude. Cluster analysis forspecies and habitat used NTSYSpc 2.10p. programs for Jaccard similarity index revealed6 groups of species and habitats respectively.Keywords: ecology, landsnail, biodiversity, density, cluster